Fish pre-acclimation temperature only modestly affects cadmium toxicity in Atlantic salmon hepatocytes. (April 2016) - Olsvik, Pål A.; Søfteland, Liv; Hevrøy, Ernst M.; Rasinger, Josef D.; Waagbø, Rune
Abstract: An emerging focus in environmental toxicology is how climate change will alter bioavailability and uptake of contaminants in organisms. Ectothermic animals unable to adjust their temperature by local migration, such as farmed fish kept in net pens, may become more vulnerable to contaminants in warmer seas. The aim of this work was to study cadmium (Cd) toxicity in cells obtained from fish acclimated to sub-optimal growth temperature. Atlantic salmon hepatocytes, harvested from fish pre-acclimated either at 15 °C (optimal growth temperature) or 20 °C (heat-stressed), were exposed in vitro to two concentrations of Cd (control, 1 and 100 µM Cd) for 48 h. Cd-induced cytotoxicity, determined with the xCELLigence system, was more pronounced in cells from fish pre-acclimated to a high temperature than in cells from fish grown at optimal temperature. A feed spiked with antioxidants could not ameliorate the Cd-induced cytotoxicity in cells from temperature-stressed fish. At the transcriptional level, Cd exposure affected 11 out of 20 examined genes, of which most are linked to oxidative stress. The transcriptional levels of a majority of the altered genes were changed in cells harvested from fish grown at sub-optimal temperature. Interaction effects between Cd exposure and fish pre-acclimation temperature were seen for four transcripts, hmox1, mapk1, fth1 and mmp13 . Overall, this study shows that cells from temperature-stressed fish are modestly more vulnerable to Cd stress, and indicate that mechanisms linked to oxidative stress may be differentially affected in temperature-stressed cells. Highlights: We examined Cd toxicity in cells from temperature-stressed fish. Cd-induced cytotoxicity was higher in cells from temperature-stressed fish. Fish pre-acclimation temperature affected oxidative stress genes. Cells from temperature-stressed fish were modestly more vulnerable to Cd stress.